The view from the cheap seats : selected non-fiction - Gaiman, Neil. (London : Headline publishing group, 2016)
The View From the Cheap Seats will draw you in to these exchanges on making good art and Syrian refugees, the power of a single word and playing the kazoo with Stephen King, writing about books, comics and the imagination of friends, being sad at the Oscars and telling lies for a living. Here 'we can meet the writer full on' (Stephen Fry) as he opens our minds to the people he admires and the things he believes might just mean something - and makes room for us to join the conversation too.
Some things I believe. Credo ; Why our future depends on libraries, reading and daydreaming : the Reading Agency Lecture, 2013 ; Telling lies for a living...and why we do it : the Newbery Medal Speech, 2009 ; Four bookshops ; Three authors : on Lewis, Tolkien and Chesterton : the MythCon 35 Guest of Honor Speech ; The pornography of genre, or the genre of pornography ; Ghosts in the machines : some Hallowe'en thoughts ; Some reflections on myth (with several digressions onto gardening, comics and fairy tales) ; How dare you : on America, and writing about it ; All books have genders ; The PEN Awards and Charlie Hebdo ; What the [very bad swearword] is a children's book, anyway? The Zena Sutherland Lecture -- Some people I have known. These are not our faces ; Reflections : on Diana Wynne Jones ; Terry Pratchett : an appreciation ; On Dave McKean ; How to read Gene Wolfe ; Remembering Douglas Adams ; Harlan Ellison : The Beast That Shouted Love at the Heart of the World ; Banging the drum for Harlan Ellison ; On Stephen King, for the Sunday Times ; Geoff Notkin : meteorite man ; About Kim Newman, with notes on the creation and eventual dissolution of the Peace and Love Corporation ; Gumshoe : a book review ; SIMCITY ; Six to six -- Introductions and musings : science fiction. Fritz Leiber : the short stories ; Hothouse ; Ray Bradbury, Fahrenheit 451 and what science fiction is and does ; Of time, and Gully Foyle : Alfred Bester and The Stars My Destination ; Samuel R. Delany and The Einstein Intersection ; On the fortieth anniversary of the Nebula Awards : a speech, 2005 -- Films and movies and me. The Bride of Frankenstein ; MirrorMask : an introduction ; MirrorMask : a Sundance diary ; The nature of the infection : some thoughts on Doctor Who ; On comics and films : 2006 -- On comics and some of the people who make them. Good comics and tulips : a speech ; A speech to professionals contemplating alternative employment, given at PROCON, April 1997 ; "But what has that to do with Bacchus?" Eddie Campbell and Deadface ; Confessions : on Astro City and Kurt Busiek ; Batman : Cover to Cover ; Bone : an introduction, and some subsequent thoughts ; Jack Kirby : king of comics ; The Simon and Kirby Superheroes ; The spirit of seventy-five ; The Best of the Spirit ; Will Eisner : New York stories ; The keynote speech for the 2003 Eisner Awards ; 2004 Harvey Awards speech ; The Best American Comics, 2010 -- Introductions and contradictions. Some strangeness in the proportion : the exquisite beauties of Edgar Allan Poe ; On The New Annotated Dracula ; Rudyard Kipling's Tales of Horror and Fantasy ; From the days of future past : The Country of the Blind and Other Stories, by H.G. Wells ; Business as usual, during alterations : Information Doesn't Want to Be Free, by Cory Doctorow ; The mystery of G.K. Chesterton's Father Brown ; Concerning dreams and nightmares : the dream stories of H.P. Lovecraft ; On The 13 Clocks by James Thurber ; Votan and Other Novels by John James ; On Viriconium : some notes toward an introduction ; So Long, and Thanks for All the Fish : an introduction ; Dogsbody by Diana Wynne Jones ; Voice of the Fire by Alan Moore ; Art and Artifice by Jim Steinmeyer ; The Moth : an introduction -- Music and the people who make it. Hi, by the way : Tori Amos ; Curious wine : Tori Amos II ; Flood : Twenty-fifth Anniversary Edition, They Might Be Giants ; Lou Reed, in memoriam : "The Soundtrack to My Life" ; Waiting for the man : Lou Reed ; Afterword afterword : Evelyn Evelyn ; Who Killed Amanda Palmer -- On 'Stardust' and fairy tales. Once upon a time ; Several things about Charles Vess ; The King of Elfland's daughter, Lord Dunsany ; Lud-in-the-Mist ; The thing of it is : Jonathan Strange and Mr. Norrell ; On Richard Dadd's The Fairy-Feller's Master-Stroke -- Make good art. Make good art -- The view from the cheap seats : real things. The view from the cheap seats ; A wilderness of mirrors ; The Dresden dolls : Hallowe'en 2010 ; Eight views of Mount Fuji : Beloved Demons and Anthony Martignetti ; So many ways to die in Syria now : May 2014 ; A Slip of the Keyboard : Terry Pratchett.
Includes index.
Keywords: Creative nonfiction; English essays -- 21st century; Popular culture; Essays; Literature